Wir haben uns für einen anderen Kandidaten entschieden. – Zu den Argumentationsmustern in den deutschen Absageschreiben auf Bewerbungen - Szczęk, Joanna (Studia Germanica Posnaniensia, 2019)
The subject of this analysis are German job application refusal letters, in which a number of structural elements can be distinguished. One of them is argumentation or justification. This text studies logical argumentation strategies and its objective is to create a typology of justifications in job application refusal letters.